Aktor Penghubung Dalam Modular Parties - Dewi Suteja, I Gusti Ayu Sintya; -, Bandiyah; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2021)
This study aims to determine the relationship between PKS and Bambang Santoso with mass mobilization through Mudjiono in the Legislative Election 2019. This study uses the Modular Parties theory by Novaes to see brokers as free agents who can mobilize their voter linkages because they receive more profitable proposals. The research method used is descriptive qualitative using primary data and secondary data because the topic is complex and closely related to social interaction. The results of this study are: first, when there is a conflict within the PKS, the relationship that exists between the PKS and Mudjiono is no longer mutually beneficial, so Mudjiono chooses to leave and has a detrimental impact on the PKS. Second, Mudjiono's relationship with Bambang Santoso is mutually beneficial because Bambang Santoso gets votes from Mudjiono's voter network, while for Mudjiono, the closer he is to power, the stronger his position as a broker. Keywords : Mudjiono, Broker, Modular Parties, Legislative Election in 2019